Does the Covid-19 Vaccine Guarantee Students in Indonesia Willing to Study Offline? - Eka Hendi Andriansyah; M. Riadhos Solichin; Deddy Setiawan; Vina Budiarti Mustika Sari; Siti Mazilatus Sholikha; Naning Eko Noviana; Muhammad Miftah Farid (IKIP Widya Darma Surabaya, 2023)
The Covid 19 pandemic brought changes to all aspects of people's social life. The obligation to carry out vaccines as a way of preventing this virus is growing and is mandatory for children to adulthood. Learning activities carried out online during the Covid 19 pandemic changed students' thoughts and habits that learning can be done online and they began to feel comfortable in these educational activities. However, is the administration of vaccines able to restore public confidence to return to activities, especially carrying out education offline? This study explores information about whether students in Indonesia are willing to study offline after receiving the COVID-19 vaccine. The author uses a quantitative approach to get this answer. 3449 respondents who are students in all provinces of Indonesia were taken randomly through a questionnaire. The results of the study said that students are willing to study offline when they have been vaccinated against Covid-19. Other results state that older students are increasingly reluctant to be vaccinated (Gitiyarko, 2020). The novelty of this study is that researchers are trying to find answers to students' enthusiasm for offline lectures which must later be carried out after the Covid 19 pandemic and this research has never been researched by previous research